2010
DOI: 10.1002/app.31386
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chemical structure and properties of a perfluorosulfonated acid membrane induced by fuel‐cell operation

Abstract: Changes in a perfluorosulfonated acid polymer membrane in membrane electrode assemblies were studied after different times under stationary conditions in fuel cells. A large series of characterizations demonstrated changes in the morphology, mechanical behavior, and thermal stability upon aging. Overall, the membrane evolution could be mainly attributed to both chemical degradation and cationic contamination. The reduction in the membrane thickness, detected by scanning electron microscopy, was ascribed to a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(86 reference statements)
1
21
0
Order By: Relevance
“…The nature and amount of cationic contaminants within a aged PFSA membrane can be determined by performing FTIR analyses, preferentially in transmission mode. According to Figure , which gathers a broad series of results from the literature, the position of the peaks at υtrue‾ = 970 and 1060 cm −1 in a FTIR spectrum usually attributed to SO 3 − and COC moieties, respectively gives enough information to target the possible cations that induced a contamination of the membrane during PEMFC operation …”
Section: Degradation Of the Membranementioning
confidence: 99%
“…The nature and amount of cationic contaminants within a aged PFSA membrane can be determined by performing FTIR analyses, preferentially in transmission mode. According to Figure , which gathers a broad series of results from the literature, the position of the peaks at υtrue‾ = 970 and 1060 cm −1 in a FTIR spectrum usually attributed to SO 3 − and COC moieties, respectively gives enough information to target the possible cations that induced a contamination of the membrane during PEMFC operation …”
Section: Degradation Of the Membranementioning
confidence: 99%
“…The water uptake (WU) of the samples was determined by the weight difference between the hydrated membranes and dry membranes . The dry membrane weight ( W dry ) was measured after drying the samples at 130°C for 18 h in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, to date, water permeation studies have largely been restricted to pristine membranes and relatively few studies have attempted to measure the water uptake of degraded Nafion ® membranes. The majority of studies of water uptake of degraded membranes that have been reported are carried out at ambient temperature [35,42,43] but such conditions are not reflective of fuel cell operating conditions (40e100% RH and 60e80 C). In this report, we examine the effect of membrane degradation on water transport performed using ex-situ measurements.…”
Section: Introductionmentioning
confidence: 99%